Agrotis segetum - Rybalkin, Sergey A. (Zenodo, 2020)
Agrotis segetum (Denis & Schiffermüller, 1775) Fig. 3: 24 fig. 4: 25 Material. Russia: Kunashir Island, 4.5 km NW Mendeleyevo Airport, Tretyakovo village, 7.07– 30.07.2015, 17 ex. , 1.09– 22.09.2019, 5 ex., leg. S. Rybalkin. Distribution. Russia (Kamchatka, Khabarovsky Krai, Sakhalin, Amur Region, Kuril Islands (Shikotan Island), Primorsky Krai, Yakutia, S. Siberia, W. Siberia, Ural, European Russia, N. Caucasus), Japan (Hokkaido, Honshu, Shikoku, Kyushu), Korea, China, Taiwan, Mongolia, Kazakhstan, Middle Asia, Near East, Baltic countries, Belarus, Ukraine, Europe, SE. Asia, India, Nepal, Africa (Lelej 2016). The species is recorded for the first time from Kunashir Islands. Published as part of Rybalkin, Sergey A., 2020, On the knowledge of Lepidoptera of Kunashir Island, Russia, pp. 98-105 in Amurian Zoological Journal XII (2) on page 105, DOI:10.33910/2686-9519-2020-12-2-98-105, http://zenodo.org/record/11362013